2014
DOI: 10.15171/bi.2014.006
|View full text |Cite
|
Sign up to set email alerts
|

Association of CRP gene polymophism with CRP levels and coronary artery disease in type 2 diabetes in Ahwaz, Southwest of Iran

Abstract: Introduction: We evaluated the association between four polymorphisms in the CRP gene with serum C-reactive protein (CRP) levels, prevalence and severity of coronary artery disease (CAD) in type 2 diabetes mellitus (T2DM) patients. Methods: We performed coronary angiography for 308 T2DM patients and classified them into two groups: T2DM with CAD and T2DM without CAD. All patients were from Ahvaz, Iran. serum levels of CRP, glucose and lipid profile were measured. Genotyping was performed by PCR/RFLP, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…A total of 150 participants without coronary arteries stenosis were selected as the control group and 142 ones with more than 50% blockage of one of the coronary arteries as the case group. Inclusion and exclusion criteria for the participants and the criteria for determining the stenosis of the coronary arteries have already been published in another article (33). After fasting for 12 hours, 5 ml blood sample was obtained in non-EDTA tubes from each person for plasma preparation and 2 ml was taken in EDTA tube for DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 150 participants without coronary arteries stenosis were selected as the control group and 142 ones with more than 50% blockage of one of the coronary arteries as the case group. Inclusion and exclusion criteria for the participants and the criteria for determining the stenosis of the coronary arteries have already been published in another article (33). After fasting for 12 hours, 5 ml blood sample was obtained in non-EDTA tubes from each person for plasma preparation and 2 ml was taken in EDTA tube for DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Based on genome-wide association studies (GWASs) relevant to CRP [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], the SNPs that could affect serum level of CRP were selected and included in this investigation. We also included SNPs with a confirmed association with inflammatory disorders [39][40][41][42][43]. Finally, rs11265260, rs1205, rs12093699, rs1800947, rs2794520, rs1341665, rs3093059, rs3093068, rs3122012, rs7553007, and rs1130864 were assessed in this study.…”
Section: Selection Of Genetic Locimentioning
confidence: 99%
“…For instance, it has been reported that the coagulation system and complement system participate in the mast cell activation in CSU patients . C‐reactive protein (CRP), encoded by the CRP gene, is greatly increased during infection, acute injury and autoimmune‐related diseases . CRP is regarded as an acute phase protein (APP) in the course of mast cell degranulation and complement system activation in the coagulation system .…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] C-reactive protein (CRP), encoded by the CRP gene, is greatly increased during infection, acute injury and autoimmune-related diseases. [17] CRP is regarded as an acute phase protein (APP) in the course of mast cell degranulation and complement system activation in the coagulation system. [18][19][20][21] CRP is correlated with the disease severity of CSU.…”
Section: Introductionmentioning
confidence: 99%